16 kDa prolactin reduces angiogenesis, but not growth of human breast cancer tumors in vivo - Faupel-Badger, J.M. (2010)
Prolactin (PRL) is a peptide hormone necessary for normal growth and development of the human breast. In addition, high levels of PRL in plasma correlate with increased risk of breast cancer, especially among postmenopausal women. Several isoforms of PRL exist in human circulation, including a 16 kDa isoform that is an N-terminal fragment of the full-length 23 kDa PRL. 16 kDa PRL has been shown to be anti-angiogenic in vitro and in vivo, and to reduce formation of tumors from prostate, colon and melanoma cancer cell lines. Here we explore the effect of 16 kDa PRL expression in vitro and in vivo using two breast cancer cell line models (MCF-7 and MDA-MB-231) and also the HCT-116 colon cancer cell line. In all three cell lines, 16 kDa PRL expression inhibited cell proliferation in vitro compared to empty vector controls. In vivo results were markedly different between the two types of cell lines. HCT-116 cells expressing 16 kDa PRL exhibited reduced vascularization and tumor formation, consistent with published results. The breast cancer cell lines expressing 16 kDa PRL also exhibited inhibition of angiogenesis in vivo but no reduction in tumor size or formation. These results suggest that the effects of 16 kDa PRL on tumor formation may vary across tissue types. The unique sensitivity of breast cancer to PRL as a mitogen and/or additional factors in the mammary gland environment (e.g. local hormone/mitogen concentration) may play a dominant role in tumor formation in vivo, thus outweighing the anti-angiogenesis effects and in vitro reduction in cell proliferation induced by 16 kDa PRL.